Pengaruh Free Cash Flow dan Pertumbuhan Perusahaan Terhadap Kebijakan Utang Pada Perusahaan Sektor Manufaktur yang Terdaftar di Bursa Efek Indonesia Kategori LQ 45 Tahun 2013 – 2017 - Nur Fadilla; Fika Aryani (Neraca : Jurnal Akuntansi Terapan, 2019)
This study aimed to analyze the effect of the Free Cash Flow and Company Growth on Debt Policy. This study was classified quantitative research. The population in this study were manufacturing sector companies listed on the Indonesia Stock Exchange in LQ 45 category 2013 - 2017. The sampling technique was saturated sampling with a population of 9 companies and 40 samples. The analysis used was descriptive statistics, statistical tests and multiple linear regression analysis to see the coefficient of determination, the statistical F value and the statistical t value used in the hypotheses test. The results of this study showed that free cash flow has a partially positive and significant effect on debt policy, with a significance level of 0.004 < 0.05. The company's growth has no effect on debt policy with a significance level of 0.125 > 0.05. The two variables Simultaneously affect debt policy. This was based on the value of F count 5.642 > F table 3.25 with a significance level of 0.007 < 0.05. Predictive ability of the two variables on debt policy is 19.2% while the remaining 80.8% is affected by other factors not included in the research model.